Algunas experiencias en el uso de las calculadoras en la enseñanza y aprendizaje de la matemática en Costa Rica (ING) - Faria, Edison De; Castro, Anabelle (Uniciencia, 2003)
The purpose of this paper is to present results about experiences in the Colegio Científico de San Carlos and in the Mathematics 3 for Computation course in the Universidad de Costa Rica, through the research project “Technological innovations in mathematics teaching”, designed by mathematics teachers of the public universities in Costa Rica and carried out in seven laboratories located in the following sites: The Mathematics Departments of the Universidad Nacional, Universidad Estatal a Distancia, Instituto Tecnológico de Costa Rica, Universidad de Costa Rica and the Colegios Científicos Costarricenses in Pérez Zeledón, San Carlos and San Pedro.